Strategi Pemasaran Politik Lis Darmansyah - Raja Ariza dalam Pilkada (Pilkwako) Tanjungpinang - Jodi Risky Novriwan Sianturi; Joko Apriadi; Syahrul Nizam (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This study aims to analyze the political marketing strategies employed by the candidate pair Lis Darmansyah and Raja Ariza in the 2024 Tanjungpinang Mayor Election. The research focuses on the implementation of the political marketing mix, which includes political products, promotion, pricing, and distribution strategies. The study uses a qualitative descriptive approach, with data collected through interviews, field observations, and documentation involving campaign teams, volunteers, and voters. The findings demonstrate that Lis Darmansyah and Raja Ariza's political marketing strategy primarily depends on social interaction and personal image creation through the use of social media platforms, in- person campaigns, and local volunteer networks. The secret to winning over voters is their attempt to present an image of inclusive and seasoned leadership. However, the public's opinion of previous political performance and fierce electoral competition present obstacles for the campaign. In conclusion, the capacity of candidates to gain the public's trust and modify their political messaging to fit the social and cultural dynamics of Tanjungpinang community is a major factor in the efficacy of political marketing techniques.